Asian American elders in the twenty-first century key indicators of well-being - Mui, Ada C. 1949- (Columbia University Press, 2008)
Asian Americans make up a diverse ethnic group in the Unites States and are among the fastest growing population of adults sixty-five years and older. Most Asian Americans are either first-generation immigrants who grew up in the United States or individuals who joined their American families later in life. Yet despite the significant presence of Asian Americans in this country, adequate resources tracking their health over the life span are surprisingly scarce. With this book, Ada C. Mui and Tazuko Shibusawa provide necessary data on the psychosocial well-being of Asian American elders. Focusing on the six largest Asian American groups (Chinese, Filipino, Indian, Japanese, Korean, and Vietnamese), they address issues relating to methodology, physical and mental health, intergenerational relationships, informal support, acculturation, stress, economic well-being, productive aging, and the utilization of services, such as Medicare, food stamps, physician care, home health care, community-based outreach, and emergency rooms and hospitals. By linking research findings to policy, practice, and program recommendations, Mui and Shibusawa create a vital resource that can be used in multiple disciplines, including social work, public health, nursing, geriatric medicine, social policy, and other helping professions. No other text offers such a comprehensive and up-to-date portrait of the unique challenges facing Asian Americans as they age.